Left ventricular hemodynamic forces as a marker of mechanical dyssynchrony in heart failure patients with left bundle branch block - Jonatan Eriksson (Nature Portfolio, 2017)
Abstract Left bundle branch block (LBBB) causes left ventricular (LV) dyssynchrony which is often associated with heart failure. A significant proportion of heart failure patients do not demonstrate clinical improvement despite cardiac resynchronization therapy (CRT). How LBBB-related effects on LV diastolic function may contribute to those therapeutic failures has not been clarified. We hypothesized that LV hemodynamic forces calculated from 4D flow MRI could serve as a marker of diastolic mechanical dyssynchrony in LBBB hearts. MRI data were acquired in heart failure patients with LBBB or matched patients without LBBB. LV pressure gradients were calculated from the Navier-Stokes equations. Integration of the pressure gradients over the LV volume rendered the hemodynamic forces. The findings demonstrate that the LV filling forces are more orthogonal to the main LV flow direction in heart failure patients with LBBB compared to those without LBBB during early but not late diastole. The greater the conduction abnormality the greater the discordance of LV filling force with the predominant LV flow direction (r2 = 0.49). Such unique flow-specific measures of mechanical dyssynchrony may serve as an additional tool for considering the risks imposed by conduction abnormalities in heart failure patients and prove to be useful in predicting response to CRT.